Erythrocyte selenium concentration predicts intensive care unit and hospital mortality in patients with septic shock: a prospective observational study - Costa, Nara Aline [UNESP]; Gut, Ana Lúcia [UNESP]; Coelho Pimentel, Jose Alexandre; Franciscato Cozzolino, Silvia Maria; Gaiolla, Paula Schmidt Azevedo [UNESP]; Fernandes, Ana Angelica Henrique [UNESP]; Polegato, Bertha Furlan [UNESP]; Tanni, Suzana Erico [UNESP]; Gaiolla, Rafael Dezen [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP]; Minicucci, Marcos Ferreira [UNESP] (Biomed Central Ltd, 2014)
Introduction: Selenoenzymes can modulate the extent of oxidative stress, which is recognized as a key feature of septic shock. The pathophysiologic role of erythrocyte selenium concentration in patients with septic shock remains unknown. Therefore, the objective of this study was to evaluate the association of erythrocyte selenium concentration with glutathione peroxidase (GPx1) activity, GPx1 polymorphisms and with ICU and hospital mortality in septic shock patients.Methods: This prospective study included all patients older than 18 years with septic shock on admission or during their ICU stay, admitted to one of the three ICUs of our institution, from January to August 2012. At the time of the patients' enrollment, demographic information was recorded. Blood samples were taken within the first 72 hours of the patients' admission or within 72 hours of the septic shock diagnosis for determination of selenium status, protein carbonyl concentration, GPx1 activity and GPx1 Pro198Leu polymorphism (rs 1050450) genotyping.Results: A total of 110 consecutive patients were evaluated. The mean age was 57.6 +/- 15.9 years, 63.6% were male. Regarding selenium status, only erythrocyte selenium concentration was lower in patients who died in the ICU. The frequencies for GPx1 Pro198Leu polymorphism were 55%, 38% and 7% for Pro/Pro, Pro/Leu and Leu/Leu, respectively. In the logistic regression models, erythrocyte selenium concentration was associated with ICU and hospital mortality in patients with septic shock even after adjustment for protein carbonyl concentration and acute physiology and chronic health evaluation II score (APACHE II) or sequential organ failure assessment (SOFA).Conclusions: Erythrocyte selenium concentration was a predictor of ICU and hospital mortality in patients with septic shock. However, this effect was not due to GPx1 activity or Pro198Leu polymorphism.